Myristica fragrans and Chronic Toxoplasmosis; In Vivo Parasitological, Histopathological and SEM Study - Noha Madbouly Taha; Maysa Mohamed Kamel Sobhy; Rabab Sayed Zalat; Mohamed Sherif Ismail Negm; Eman Ahmed EL-wakil; Dina M. H. El Akkad (Journal of Global Pharma Technology, 2020)
Toxoplasma gondii (T.gondii) is one of the most important protozoa causing abortion in pregnant women and fatal manifestations in immunocompromized individuals. The present study was conducted to assess the effect of Myristica fragrans (M.fragrans) alone and loaded on Chitosan nano particles (CS NPs) on chronic toxoplasmosis as a more effective safe candidate in comparison with spiramycin. One hundred and ten laboratory bred Swiss albino mice were infected by oral inoculation of T.gondii tissue cysts, treated for 14 days starting from the 4th week post infection (p.i) and sacrified at the 10th week p.i. The effect of drugs was assessed by counting the number of tissue cysts in homogenized brain tissues, histopathological examination and SEM of brain tissue. There was a significant decrease in the number of tissue cysts detected in the brain between the control group and all treated groups (P<0.001). Histopathological examination revealed marked improvement of inflammation in all treated groups and the SEM of brain tissues revealed remarkable changes in the shape and structure of the T.gondii tissue cysts.